Correlation between response time and infant outcome in pregnant women with fetal distress undergoing caesarean section in two tertiary hospitals - Raditya Ery Pratama; M Ardian CL (Majalah Obstetri dan Ginekologi, 2021)
Objectives: This study aimed to illustrate the response time of pregnant women with fetal distress undergoing caesarean section at dr. Soetomo Hospital and Universitas Airlangga Hospital during 2015-2017.Materials and Methods: This was a non-experimental descriptive observational study using medical records at dr. Soetomo Hospital and Universitas Airlangga Hospital during 2015-2017. Samples of the study were enrolled using total sampling.Results: Data at dr. Soetomo Hospital revealed 103 patients: the age characteristics of >30 year were 48 patients (38%), underlying diseases with hypertension 68 cases (66%), use of general anesthesia with 65 cases (63%). Caesarean section response time >30 minutes was in 85 cases (83%), from which 58 babies (56.3%) had severe asphyxia. At Universitas Airlangga Hospital there were 5 patients, from whom those of 20-30 years were 4 (80%), and those with underlying diseases of hypertension were 3 patients (60%), and those using general anesthesia were 4 (80%). caesarean section response time of >30 minutes were in 3 cases (60%) where all 5 babies (100%) had moderate asphyxia. Age data processing with Chi-square test revealed p = 0.534 (p>0.05), indicating no significant relationship between age group with fetal outcome. Response time of the caesarean section showed p = 0.027 (p<0.05), indicating significant relationship between caesarean section response time and fetal outcome.Conclusion: Response time of pregnant women with fetal distress performed caesarean section at dr. Soetomo Hospital and Universitas Airlangga Hospital period 2015-2017 was still more than 30 minutes and the baby's was found to  have moderate-severe asphyxia. These were due to delayed informed consent, patient stabilization, as well as anesthesia, operating room and pediatrics preparation.